Peer review of the pesticide risk assessment for the active substance fluquinconazole in light of confirmatory data submitted - European Food Safety Authority (EFSA) (EFSA Journal, 2016)
Abstract The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State Ireland, for the pesticide active substance fluquinconazole are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory ecotoxicology data. The conclusions were reached on the basis of the evaluation of the representative uses of fluquinconazole as a fungicide on wheat. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Concerns are identified.